Toward effectiveness and authenticity in PBL: A proposal based on a virtual learning environment in computing education. Issue 2 (29th November 2018) - Bessa, Bruno R.; Santos, Simone; Duarte, Breno J.
Abstract: Problem‐Based Learning (PBL) has gained widespread approval as a constructive, student‐centered approach to teaching, and learning. Advocating the use of real‐life problems to initiate and motivate the learning process, PBL is an inductive strategy promoting the understanding of new concepts as well as the development of professional skills, abilities, and attitudes. Thus, it is paramount that teachers and students implement PBL in conformity to its core principles. However, such implementation becomes a challenge, considering that PBL is fundamentally different from traditional instruction methods. Without the appropriate pedagogical and technological support, PBL's quality, effectiveness, and authenticity are at risk. In an attempt to overcome these challenges, this paper presents the PBL‐Coach Virtual Learning Environment (VLE), built upon PBL learning theories. This paper describes in detail a scientific investigation on a practical PBL implementation, driven by the quest to achieve the following goals: (i) Scaffold teachers and students in implementing the PBL method; (ii) Investigate useful and usable technological resources in the PBL process; (iii) Maintain PBL core principles for an authentic and effective learning process. As a result, three case studies are described and one is detailed to validate our investigation, consisting of a real‐world setting with clients, teachers, tutors, and students. Each case study provided a good level of evidence that PBL‐Coach, used in a real‐world, authentic setting, can promote an effective learning process through a number of carefully designed technological resources. Encouraging results motivated to evolve PBL‐Coach through Augmented and Virtual Reality components as future works.